AB0149 Prolactin and autophagy in systemic lupus erythematosus: clinical significance of correlation between PRL-R+ (receptor), CD19+, ATG14+, and CD25+ expression on B and T regulatory cells. (15th June 2017) - Jara, L; Zurita, E; Durán, A; Medina, G; Arroyo, C; Saavedra, MA; Sanchez, A; Bustamante, R; Rodriguez, A
Abstract : Background: Systemic Lupus Erythematosus (SLE) is a prototype of autoinmune diseases with excessive anti-nuclear autoantibodies production. B cells activation with immune complex formation is the main characteristic of SLE with abnormalities in immune cells, dysregulation of apoptosis, and defects in the clearance of apoptotic materials. Autophagy, a highly conserved protein degradation pathway, is essential for removing protein aggregates and misfolded proteins in cells and its defects contributes to SLE pathogenesis. On the other hand, multiple evidences in humans and experimental models suggest that prolactin (PRL) is associated with active SLE and participates in the immune dysregulation, and one of the mechanisms of PRL action is the inhibition of apoptosis. Objectives: Analyze the relationship between PRL receptors (PRL-R) on B cells and markers of autophagy on T regulatory cells and the association, if any, with clinical characteristics of SLE. Methods: The expression of PRL-R on B cells CD19 +, and autophagy-related key regulator protein ATG14 +, on T regulatory cells CD25 +, were measured by flow cytometry, and expressed in percentages of SLE patients (1997, ACR criteria), and healthy controls. Active SLE was considered by SLEDAI (≥4). The organs affected and treatments were evaluated. Results: A total of 40 SLE patients and 20 healthy controls were included. Mean age of patients and controls was 30.67±4.16. Mean duration of disease was 6±4.6 years. Twenty patients were active (SLEDAI 8.45±1.9) and of these, lupus glomerulonephritis was observed in 13 patients (65%). The expression of PRL-R on B cells of active SLE was higher than in inactive SLE (50.5% vs 26.5%). In active SLE especially in patients with glomerulonephritis, the mean amount of PRL-R on B cells/ml was 6, 645/ml (range 3167–6957). In contrast, patients with inactive SLE, had a low amount of PRL-R, 522.5/ml (range 15–895). In the relation of autophagy, the mean expression of ATG14 + in 20 active SLE patients was 11.19% in comparison with inactive SLE patients, 7.13%, (p=0.04), and in healthy donors, 7.445% (p=0.0281). Conclusions: Our study suggest: In active SLE patients the expression of PRL-R and autophagy-related key regulator protein ATG14+ are very high in B cells and T regulators respectively, in comparison with inactive SLE and healthy donors. These novel findings suggest the interaction between PRL-R and autophagy in order to promote clinical/immune activation with overproduction of autoantibodies. PRL-R and ATG14 + may be a new target of SLE treatment. References: Lech M, Anders HJ, The pathogenesis of lupus nephritis. J Am Soc Nephrol, 2013, 24, 1357–1366. Jara LJ, Medina G, Saavedra MA, et al. Prolactic has a patogenyc role in systemic lupus erythematosus, Inmmunol Res, 2017, Jan 28. Disclosure of Interest: None declared